2012
DOI: 10.4238/2012.may.15.3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and single nucleotide polymorphism analysis of IGF2a genes in the common carp (Cyprinus carpio)

Abstract: ABSTRACT. We studied whether two IGF2 transcripts in common carp are similar to those found in zebrafish. The full-length IGF2a cDNA contains a 5'-terminal untranslated region (UTR) of 105 bp, a 3'-terminal UTR of 1358 bp and an open reading frame of 612 bp, which encodes a 206-amino acid protein. A 6614-bp full-length IGF2a DNA molecule, including the 5'-flanking region, was isolated. Genomic DNA structure analysis revealed that the IGF2a gene contains four exons and three introns. Bioinformatics analysis ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The genome structure of igf2 of L. maculatus comprised four exons and three introns ( Figure 2 ). This structure is consistent with that of other fish types, including largemouth bass ( Micropterus salmoides ), common carp ( Cyprinus carpio ), salmon ( Oncorhynchus keta ), tilapia ( Oreochromis niloticus ), Asian sea bass ( Lates calcarifer ), and pike perch ( Sander lucioperca ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. This result indicates that the structure of the igf2 genome of fish is relatively conserved.…”
Section: Discussionsupporting
confidence: 83%
“…The genome structure of igf2 of L. maculatus comprised four exons and three introns ( Figure 2 ). This structure is consistent with that of other fish types, including largemouth bass ( Micropterus salmoides ), common carp ( Cyprinus carpio ), salmon ( Oncorhynchus keta ), tilapia ( Oreochromis niloticus ), Asian sea bass ( Lates calcarifer ), and pike perch ( Sander lucioperca ) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. This result indicates that the structure of the igf2 genome of fish is relatively conserved.…”
Section: Discussionsupporting
confidence: 83%
“…Two IGF2 sequences ( IGF2a and IGF2b ) were annotated in this region of the common carp genome (Xu et al, 2014b). As most mammals and teleost fishes possess only one IGF2 gene copy, in order to assess the (dis)similarity of these two sequences, Su et al cloned IGF2a and aligned it with IGF2b , and proposed homology between these paralogs in common carp and zebrafish (Su et al, 2012). We aligned the two genomic regions containing these two genes, including the upstream and downstream sequences, and found a high similarity of the two paralogs to their zebrafish orthologs (Figure 4C).…”
Section: Resultsmentioning
confidence: 99%
“…Most tetrapods harbor a single bmp2 gene, while two bmp2 genes are reportedly presented in teleosts [27]. Previous studies have shown that the bmp2b gene has the highest expression level in the muscles of common carp (Cyprinus carpio) [28]. Furthermore, the bmp2a gene is highly expressed in calcified bone tissue of the gilthead seabream (Sparus aurata) [29] and in the ovaries of African clawed frogs (Xenopus laevis) [30].…”
Section: Introductionmentioning
confidence: 99%